2009
DOI: 10.1016/j.jcrysgro.2009.03.043
|View full text |Cite
|
Sign up to set email alerts
|

On favorable thermal fields for detached Bridgman growth

Abstract: The thermal fields of two Bridgman-like configurations, representative of real systems used in prior experiments for the detached growth of CdTe and Ge crystals, are studied. These detailed heat transfer computations are performed using the CrysMAS code and expand upon our previous analyses [14] that posited a new mechanism involving the thermal field and meniscus position to explain stable conditions for dewetted Bridgman growth. Computational results indicate that heat transfer conditions that led to success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…The heat transfer computations showed that stable operating states exist with a narrow gap width but that the temperature field near the meniscus is sensitive to gap thermal conditions. Notably, the melt near the meniscus-ampoule wetting point could become supercooled under certain conditions, consistent with our prior analyses [32,62]. These phenomena certainly merit further study, since undercooling could lead to reattachment of the crystal to the ampoule wall.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The heat transfer computations showed that stable operating states exist with a narrow gap width but that the temperature field near the meniscus is sensitive to gap thermal conditions. Notably, the melt near the meniscus-ampoule wetting point could become supercooled under certain conditions, consistent with our prior analyses [32,62]. These phenomena certainly merit further study, since undercooling could lead to reattachment of the crystal to the ampoule wall.…”
Section: Discussionsupporting
confidence: 84%
“…Another effect is a flattening of the crystal-melt interface near the TPL, which causes a transition from a concave interface to a slightly convex one in the vicinity of the TPL. A similar heat transfer situation, with undercooling predicted along the meniscus during detached Bridgman growth, was first noted by Stelian et al [32,62].…”
Section: Heat Transfer Analysissupporting
confidence: 76%
See 2 more Smart Citations
“…This material is also extremely difficult to grow and has been the object of numerous studies: notable microgravity experiments by Larson et al. [1][2][3][4] on USML-1/STS-50 and USML-2/STS-73, and by Fiederle, Duffar and co-workers 5,6 on AGHF1/STS-95; experiments in terrestrial conditions [7][8][9][10][11][12][13][14][15] using floating zone, traveling heater method, horizontal Bridgman, high-pressure vertical Bridgman, detached Bridgman techniques; and extensive modeling by Derby et al [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] , Duffar and Sylla 12,33 . Cadmium telluride and its alloys have unusual thermophysical properties which make their growth very different from other semiconductor crystals.…”
Section: Introductionmentioning
confidence: 99%